The new institutional economics of corruption - Lambsdorff, Johann, Graf, 1965- (Routledge frontiers of political economy ;, 2005)
This book constitutes a thorough analysis of the phenomenon of corruption, as seen from the perspective of New Institutional Economics - one of the most influential new schools of thought in the social sciences of the past decade.